Gênero e trabalho no campo da saúde mental: perspectivas de trabalhadoras de centro de convivência e cultura - Teixeira, Cristiane Neri (2022)
ABSTRACT Women's work is a fundamental component of society, contributing to the development of the fields in which it operates and in the various spheres, whether in private or public life. The incorporation of this work into public life with remuneration was based on the tripod regulations: patriarchy, religion and capitalism. The presence of women in the labor market remains marked by unequal norms in relation to men, keeping for female workers, activities that they perform in private life as their sole responsibility. Psychologists from a community health service in a municipality in the state of Minas Gerais are the participants of this study, whose general objective was to analyze how these workers understand their work in the field of mental health and the relationship between work and gender. The specific objectives were to map the motivations of these workers to act in the field of mental health and to identify possible relationships between the health condition, self-care and the sexual division of labor. Developed in a Center for Coexistence and Culture, called CECO, the qualitative study was conducted with semi-structured interviews. Thematic analysis allowed the construction of three categories: Gender and Psychology; Work at CECO; Sexual division of work. The CECO is a device that incorporates, in its conception, actions of fundamental importance for the Anti-Asylum Fight in Brazil. The purpose of social reintegration is reaffirmed as a place in the field of conquests, struggles and permanent advances and setbacks, which mental health currently experiences. The workers of this CECO make up a reality of the working woman, in a field of traditional knowledge such as Psychology, but which expands when transiting with the intersectoriality of other knowledge and skills, which enrich the professional identity, which suffers the interference of models of management and that reflect in their daily lives. The historical unequal work relations and the intense differences between sexes in the distribution of life tasks are present. By discussing the experience of these CECO workers, it is expected to contribute to making managers and society aware of the reality of a service that needs investment in several aspects, with a focus on a more robust team and isonomic working conditions. It is inevitable that this knowledge can be made visible and recognized, so that they collaborate in the construction of professionals who come to compose this social tissue, which is built on new propositions of meanings of those who are in daily work and allow the work to reveal itself with new nuances. For workers, it is a call to analyze their performance in mental health with art and culture, involving all the aspects of the female condition and how they impact their work. Descriptors: Community Mental Health Services. Women's Work. Psychology